Application of the Iqra Method in Improving Al-Qur'an Reading Ability - Nashirotun Fitriani Rahmi; Imam Tabroni (Jurnal Pengabdian Masyarakat Bestari, 2022)
The low interest in reading that occurs in children is an important reason for fostering a culture of literacy in children in Salem Village. The low level of education in a society dominated by elementary school graduates is one of the factors causing the lack of awareness of parents in briefing children on the importance of getting used to reading early because reading can be a support for the success of educational goals in Indonesia that must be used as a routine daily activity. Literacy culture is a stage in the form of the ability to read, explore, and study various information obtained to solve problems that arise in everyday life that aims to improve the quality of life. This devotion aims to improve literacy skills where the main focus is to increase interest in reading in children. This service uses a collaborative Participatory action research (PAR) design. The author collaborated with the manager of jejer Cacaka reading house located in Salem Village. The results of the devotion showed that there was an increase in reading interest in children by 90%. The improvement of literacy skills needs support from all parties so that this success can continue to be improved again.